Influence of the Method of Definition on the Prevalence of Left-Ventricular Hypertrophy in Children with Chronic Kidney Disease: Data from the Know-Ped CKD Study - Heeyeon Cho; Hyun Jin Choi; Hee Gyung Kang; Il-Soo Ha; Hae Il Cheong; Kyung Hee Han; Seong Heon Kim; Min Hyun Cho; Jae Il Shin; Joo Hoon Lee; Young Seo Park (Karger Publishers, 2017)
Background/Aims: Children with chronic kidney disease (CKD) have a high risk of cardiovascular disease. Left-ventricular (LV) hypertrophy (LVH) is an early marker of cardiovascular disease in pediatric CKD, and the prevalence of LVH in pediatric CKD is approximately 20-30% in pre-dialysis CKD patients. However, there is no consensus on the ideal method of defining LVH in pediatric CKD patients. Previous studies have typically used the LV mass index (LVMI), which is calculated as LV mass in grams divided by height in meters to the 2.7th power ≥ 38 g/m2.7, to diagnose LVH in children with CKD. Recently, age-specific reference values for LVMI ≥ 95th percentile and LV wall-thickness z-score > 1.64 in children were addressed. The aim of this study was to assess the prevalence and contributing factors of LVH in pediatric CKD patients according to each measurement and evaluate the concordance between each measurement. Methods: We used the baseline data of the KoreaN cohort study for Outcome in patients With Pediatric Chronic Kidney Disease (KNOW-Ped CKD), which is a nationwide, 10-year, prospective, observational cohort study of pediatric CKD. A total of 469 patients were enrolled, and 458 patients were included in the final analysis. Univariate and multiple logistic regression analysis were performed to evaluate the association of the variables with LVH. Kappa statistics were used to analyze the concordance. Results: According to an LVH diagnosis of LVMI ≥ 38 g/m2.7, 188 patients (41.0%) were diagnosed with LVH, and the prevalence of LVH was high in younger patients (< 2 years of age). Using the age-specific reference values, 116 patients (25.3%) were diagnosed with LVH, and there was no difference in the prevalence of LVH according to age. Thirty-one patients (6.8%) were diagnosed with LVH using an LV wall-thickness z-score > 1.64. There is poor concordance between the diagnosis of LVH using the LV wall-thickness z-score and the LVMI method. Conclusions: The results of this study show that there is poor concordance between the diagnosis of LVH using the wall-thickness z-score and the LVMI2.7 criteria. Further investigation is needed to estimate the correlation between LVH and cardiac dysfunction and to find a better method for defining LVH in the pediatric CKD cohort and thereby predicting cardiac dysfunction.